Jack of all nectars, master of most: DNA methylation and the epigenetic basis of niche width in a flower-living yeast - HERRERA, C. M.; POZO, M. I.; BAZAGA, P. (Molecular ecology, 2012)
In addition to genetic differences between individuals as a result of nucleotide sequence variation, epigenetic changes that occur as a result of DNA methylation may also contribute to population niche width by enhancing phenotypic plasticity, although this intriguing possibility remains essentially untested. Using the nectar‐living yeast Metschnikowia reukaufii as study subject, we examine the hypothesis that changes in genome‐wide DNA methylation patterns underlie the ability of this fugitive species to exploit a broad resource range in its heterogeneous and patchy environment. Data on floral nectar characteristics and their use by M. reukaufii in the wild were combined with laboratory experiments and methylation‐sensitive amplified polymorphism (MSAP) analyses designed to detect epigenetic responses of single genotypes to variations in sugar environment that mimicked those occurring naturally in nectar. M. reukaufii exploited a broad range of resources, occurring in nectar of 48% of species and 52% of families surveyed, and its host plants exhibited broad intra‐ and interspecific variation in sugar‐related nectar features. Under experimental conditions, sugar composition, sugar concentration and their interaction significantly influenced the mean probability of MSAP markers experiencing a transition from unmethylated to methylated state. Alterations in methylation status were not random but predictably associated with certain markers. The methylation inhibitor 5‐azacytidine (5‐AzaC) had strong inhibitory effects on M. reukaufii proliferation in sugar‐containing media, and a direct relationship existed across sugar × concentration experimental levels linking inhibitory effect of 5‐AzaC and mean per‐marker probability of genome‐wide methylation. Environmentally induced DNA methylation polymorphisms allowed genotypes to grow successfully in extreme sugar environments, and the broad population niche width of M. reukaufii was largely made possible by epigenetic changes enabling genotype plasticity in resource use. See also the Perspective by Schrey and Richards